2021
DOI: 10.1097/sap.0000000000002762
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Postmastectomy Radiation Therapy in Prepectoral Versus Subpectoral Autologous Breast Reconstruction

Abstract: Background Postmastectomy radiation therapy (PMRT) is known to increase the risk of multiple adverse outcomes after breast reconstruction. In the context of delayed-immediate autologous breast reconstruction, PMRT is typically conducted after placement of subpectoral (SP) tissue expanders. With the re-emergence of prepectoral (PP) reconstruction, there are little data assessing the outcomes of PP reconstruction in breasts receiving PMRT. We compared postoperative outcomes of PMRT patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Breast reconstruction in the setting of postmastectomy radiation therapy(PMRT) presents a unique challenge, because radiation therapy has an impact on the skin and soft tissues of the chest wall, leading to fibrosis that increases risks of contracture, infection, pain, necrosis, and atrophy in reconstructed tissues ( 10 ). Consequently, the discussion of the optimum operative method of breast reconstruction has not been stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction in the setting of postmastectomy radiation therapy(PMRT) presents a unique challenge, because radiation therapy has an impact on the skin and soft tissues of the chest wall, leading to fibrosis that increases risks of contracture, infection, pain, necrosis, and atrophy in reconstructed tissues ( 10 ). Consequently, the discussion of the optimum operative method of breast reconstruction has not been stopped.…”
Section: Discussionmentioning
confidence: 99%
“…65 Recent studies have shown that prepectoral breast reconstruction may be a viable option for patients who require PMRT, with comparable outcomes to subpectoral reconstruction. 66 For example, a study published in Plastic and Reconstructive Surgery Global Open found that prepectoral reconstruction had lower rates of complications and higher patient satisfaction compared to subpectoral reconstruction in patients who underwent PMRT. 67 Overall, the impact of PMRT on prepectoral and subpectoral breast reconstruction techniques continues to be an area of active research.…”
Section: Dovepressmentioning
confidence: 99%
“…Implant placement beneath the pectoralis major muscle can lead to loss of its function, known as the "contrived breast" effect, posing the need for physiotherapy [16]. Fat grafting is valuable for reducing pain and deformation animation [18,[63][64][65][66][67][68][69]. On the contrary, prepectoral placement is characterized by a lower postoperative pain and deformation animation rate.…”
Section: Patient's Perspectivementioning
confidence: 99%